Detection of Ralstonia solanacearum (Rs) in latently infected potato stem extracts by post-enrichment qPCR. - Gutarra, L.; Fuentes, S.; Kreuze, Jan F. (2012)
A sensitive method for detection of Ralstonia solanacearum in latently infected potato stem extracts has been achieved by previous enrichment procedure followed by Real time PCR (qPCR). Sensitivity of qPCR before and after enrichment (48h of incubation of the stem extract with modified SMSA broth at 30oC) was compared with other techniques such as NCM-ELISA and R.solanacearum isolation in Kelman’s medium. Before enrichment procedure, 174.6 cells/ml were detected in Kelman’s medium, 1.71 x 106 cells/ml by NCM-ELISA and 1.29x105 cells/ by qPCR. After enrichment, sensitivities of post enrichment qPCR, NCM- ELISA and isolation on modified Kelman’s medium were similar. As few as 6.56 cells/ml were detected in latently infected potato stem extracts. Serial dilutions of naturally-infected stem extract before enrichment allowed the quantification of populations of R. solanacearum in each stem extract. Post –enrichment qPCR combines the advantages of high sensitivity, ease and speed, but it requires expensive laboratory equipment. Thus it can be used by seed and breeding programmes in developing countries only to confirm positive results obtained by serological tests used for seed quality control and for assessing susceptibility of breeding lines to bacterial wilt.